The short story in Mozambique literature : post colonial writing - (:unkn) unknown (My University, 2002)
The Mozambique's short stories are clearly following a different path from the long-established western model. Crossing of voices, languages and different narrative systems, the short story puts in evidence the post-colonial African world contradictions deeply entrenching its roots in the voice of Africa.
Keywords: African Research